Developing Regional Business Incubator Activity - Ailinpieti, Heikki (2023)
Business Incubation is one of the key activities to foster new innovative scalable business creation. Globally there are several examples of successful business incubation implementations helping regions to achieve economic renewal. Kielo Growth, privately owned startup-investor, business community and angel investor family has been running business incubation since 2015 in Oulu region and support the entire Northern Finland. October 2020 Kielo Growth decided to spin-off business incubation activity to Oulu Startup Incubator. Oulu Startup Incubator was founded as a non-profit entity and at the same time first development project was started. The thesis is based on two projects, the first project was done for the Oulu Business Incubator and the second project was part of a larger Oulu University of Applied Science project. The goal of the first project was the development of a private business incubator operations. In the second project, the goal was to examine the current needs to improve business incubators co-operation in the regional innovation ecosystem. On this basis, new co-operation models and development paths were studied to meet the need for change. During the project, a significant amount of research data and other literature on different themes and incubator models and startup ecosystem evolutions are reviewed. The goal was to build a systemic understanding of what needs to be considered in the operation of a regional business incubator. During project 2, three workshops was arranged with regional stakeholders. Information about startup ecosystems in other regions in Finland and abroad was gathered. During the projects, many observations were made about the current operating environment. Business Incubation has been studied globally from many perspectives. The goal was to build overall view of business incubation to understand what the main factors are affecting establishing sustainable regional business incubation. During research and development project the biggest challenge in private business ...